Prescribing Patterns and Cost of anthihypertensive Drugs in A North Indian Internal Medicine Clinic - Hota, D; Singh, Dalbir; Sachdev, A (Nepalese Heart Journal, 2004)
Choice of antihypertensive agents depend on their efficacy to control elevated blood pressure and prevent antecedent morbidity and mortality. However, the cost of therapy also remains an important factor in deciding a particular agent. Randomly selected 300 prescriptions were analysed in a hypertension clinic. The cost were compared from the current issue of MIMS - India. Beta-blockers remain the most common agent (46.7%) fallowed by calcium channel blockers (34.3%) and ACE Inhibitors (30.0%). Diuretics were used only in 13% of prescriptions. Amongst individual agents, atenolol (36.0%), amlodipine (29.3%) and enalapril (23.0%) were most common. There is a wide variation in the annual acquisition cost for atenolol (61.4%), amlodipine (110.0%) and enalapril (55.5%). The results of the study emphasize the need for prescribing more economical brands available. Moreover, newer (and expensive) brands can be prescribed only when there is a clear indication.